Uterine Cancer Screening, Diagnosis, and Treatment (Current Clinical Oncology,, 2018)
There are more than 63,000 new cases of uterine and endometrial cancer each year in the United States, up from approximately 41,000 when the first edition of Uterine Cancer was published in 2009. A book focusing on these cancers was timely, with emergent sophistication in diagnosis increasingly impacting clinical decision-making. However, five years later, the need for an updated book on this topic is even stronger as oncologists recognize opportunities to impact the outcome on women that are increasingly diagnosed with these malignancies. Uterine Cancer: Screening, Diagnosis, and Treatment, Second Edition, part of the Current Clinical Oncology series, enhances the awareness on this somewhat neglected area of therapeutics, helping to integrate targeted therapies into the management of women with uterine cancer. Written by experts in the field in a highly practical and comprehensive manner, it is a must-have for all gynecological residents and fellows, as well as gynecological oncologists, medical oncologists, radiation oncologists, and family practice doctors who wish to provide their patients with the best possible care.